2017
DOI: 10.1039/c7ta05048h
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell zeolite Y with ant-nest like hollow interior constructed by amino acids and enhanced catalytic activity

Abstract: One-pot synthesis of core–shell zeolite Y with 3D interconnected mesochannels with enhanced crystallinity and catalytic activity by using amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…www.advancedsciencenews.com www.aem-journal.com 6800 kJ/(m 3 cycle) for thick film lanthanum zirconate stannate titanate (PLZST); [127] 7570 kJ/(m 3 cycle) for thin film YbFeO 3 (YBFO); [128] 7800 kJ/(m 3 cycle) for thick film PLZST; [129] and 8000 kJ/(m 3 cycle) for thin film 0.68PMN-0.32PT. [130] Zhang et al [131] demonstrated the significant benefits of exploiting highly aligned porosity in piezoelectric and pyroelectric materials for an improved energy harvesting performance. Novel 2-2 connectivity PZT ceramics with aligned pore channels were prepared by freeze-casting water-based PZT suspensions, with porosity levels ranging from 20 to 60 vol%.…”
Section: Pyroelectric Energy Harvestersmentioning
confidence: 99%
“…www.advancedsciencenews.com www.aem-journal.com 6800 kJ/(m 3 cycle) for thick film lanthanum zirconate stannate titanate (PLZST); [127] 7570 kJ/(m 3 cycle) for thin film YbFeO 3 (YBFO); [128] 7800 kJ/(m 3 cycle) for thick film PLZST; [129] and 8000 kJ/(m 3 cycle) for thin film 0.68PMN-0.32PT. [130] Zhang et al [131] demonstrated the significant benefits of exploiting highly aligned porosity in piezoelectric and pyroelectric materials for an improved energy harvesting performance. Novel 2-2 connectivity PZT ceramics with aligned pore channels were prepared by freeze-casting water-based PZT suspensions, with porosity levels ranging from 20 to 60 vol%.…”
Section: Pyroelectric Energy Harvestersmentioning
confidence: 99%
“…We then employed our mesoporogenic amino acids to synthesize zeolite Y, which belongs to faujasite framework with FAU topology and Si/Al ratio from 1.5 to 3. Interestingly, the natural amino acids directed the biomimetic mineralization of core‐shell mesoporous Y zeolites, as shown in Figure , which possessed an ant‐nest like hollow interior and a mechanically strong thin microporous shell. The core‐shell zeolite Y samples exhibit superior crystallinity and enhanced catalytic activity for Friedel‐Crafts benzylation of toluene, affording a yield twice that obtained over conventional zeolite Y, and also much higher than that of FAU nanosheets …”
Section: Roles Of Organic Small Moleculesmentioning
confidence: 99%
“…This is then followed by local perfection driven by thermodynamics towards equilibrium. For example, the amino acid dissociates from the weak point inside the aluminosilicate through coordinated construction actions, and gradually generates internal interconnected mesopores while maintaining the external structure of the zeolite, increasing crystallinity and mechanical strength . Usually, creation of internal void and building zeolite crystallinity are contradictory processes.…”
Section: Omega On the Crystallization Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…During the process, roots of plants actively or passively release root exudates (REs). REs contain various organic compounds such as carbohydrates, organic acids, and amino acids . These REs could provide important sources of carbon and energy for microbial growth conveniently and subsequently alter the species composition in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%